CAR T-Cell therapy for the management of mantle cell lymphoma - Zoufang Huang; Vivek P. Chavda; Rajashri Bezbaruah; Hemant Dhamne; Dong-Hua Yang; Hong-Bing Zhao (Molecular Cancer, 2023)
Abstract Mantle cell lymphoma (MCL) is a subtype of Non-Hodgkin lymphoma (NHL) of mature B-cells characterized by translocation, which is typically due to excess expression of Cyclin D1. Although with the progress in our knowledge of the causes for MCL and available treatments for MCL, this cancer is still incurable. Age, male gender, rapid advancement, significant nodal involvement, elevated serum lactate dehydrogenase level, and prognostic indications including increased expression of Ki-67 and presence of TP53 mutation, are symbols of poor outcome. Advanced immunotherapy using chimeric antigen receptor (CAR)-T cells is advantageous for patients suffering from B-cell malignancies and MCL. Targeting B-cell antigens on the cell surface is a feasible approach in re-occurring (R/R) MCL because of significant responses obtained in other B-cell cancers. USFDA has approved brexucabtagene autoleucel (Tecartus, KTE-X19), a novel CAR T-cell therapy to be used in patients with MCL who have not responded to previous treatments or have relapsed. The FDA approved this new treatment depending on the outcomes of the ZUMA-2 clinical trial. Serious adverse reactions, moderate anti-tumor activity, allergen withdrawal, antigen escape, limited tumor infiltration, and trafficking are major barriers to successful CAR T-cell therapy. This review is a brief synopsis of the development of CAR T-cell therapy for MCL.